Measuring Millennials Loyalty Through Affective and Cognitive Online Experience: Mediating Role of Customer Satisfaction - Aisah Anugerah Qadri; Yulia Hendri Yeni (Jurnal Mantik, 2021)
This paper aims to find out the direct effects of affective and cognitive OE on customer loyalty, and indirect effect through mediating role of customer satisfaction. By using the technique of purposive sampling to online questionnaires, and as many as 126 millennial groups were involved as respondents. We found that the direct effects of cognitive and affective OE significant and positively affects customer satisfaction and loyalty, while mediating roles of customer satisfaction, only to the relationship between affective OE and customer loyalty as expectation, while to the cognitive OE and customer loyalty unexpected